Work related risk factors for musculoskeletal complaints in the nursing profession: results of a questionnaire survey. Issue 9 (September 1996) - Engels, J A; van der Gulden, J W; Senden, T F; van't Hof, B
Abstract : OBJECTIVES: To determine the prevalence of musculoskeletal complaints of the back, arms or neck, and legs among nurses, and to investigate the relation between these complaints and various work related and personal variables. METHODS: A questionnaire survey was carried out in four nursing homes in The Netherlands. RESULTS: The response was 95% and resulted in 846 completed questionnaires. It was found that a large proportion of the subjects regularly had back complaints (36%) but also had arm or neck (30%) and leg complaints (16%). Almost all respondents (89%) considered nursing work as physically strenuous. Most of them complained of working under time pressure (69%), increased work pressure (70%), and having no opportunity to take a break from the work (70%). The physical variables which seem to trouble the subjects most were lifting (65%), working in awkward postures (47%), and stooping (34%). Moreover, 53% of the subjects responded that the ergonomic lay out of the ward was disagreeable. Most of the work related variables under study seemed to be associated with musculoskeletal complaints. For all types of complaints the strongest associations were found with having to lift heavy loads. Apart from physical stress various aspects of work pressure showed strong associations with the occurrence of musculoskeletal complaints. The variables on the ergonomy of the ward showed less clear associations with musculoskeletal complaints than were found for physical stress and work pressure. CONCLUSIONS: From these results it may be concluded that future research of health risks of nursing work should have a wider focus than the relation between physical workload and low back pain.